Synthesis and characterization of TiO2/ZnO-Ag@TiO2 nanocomposite and their performance as photoanode of organic Dye-Sensitized Solar Cell. (2021) - Hidayat, A.; Taufiq, A.; Supardi, Z.A.I.; Jayadininggar, S.M.; Sa'adah, U.; Astarini, N.A.; Suprayogi, T.; Diantoro, M.
Abstract: DSSC is one of the most promising energy conversion devices. A new scheme of TiO2 /ZnO-Ag@TiO2 multilayer nanocomposite was introduced as the working layer of organic DSSC. TiO2, as an inert material, was used to encapsulate Ag and applied as the photoanode. ZnO and Ag@TiO2 nanoparticles were synthesized using co-precipitation and one-pot synthesized method, respectively. The best photovoltaic parameter was performed by the highest fraction of Ag@TiO2 with the energy gap of 3.14 eV. It was appropriate that the energy gap of the films decreased as Ag@TiO2 continued to increase, thus it was influenced their photovoltaic performance.